Computer-assisted measurements of coronal knee joint laxity in vitro are related to low-stress behavior rather than structural properties of the collateral ligaments*. (22nd May 2013) - Wilson, W.T.; Deakin, A.H.; Wearing, S.C.; Payne, A.P.; Clarke, J.V.; Picard, F.
Abstract: The relationship between coronal knee laxity and the restraining properties of the collateral ligaments remains unknown. This study investigated correlations between the structural properties of the collateral ligaments and stress angles used in computer-assisted total knee arthroplasty (TKA), measured with an optically based navigation system. Ten fresh-frozen cadaveric knees (mean age: 81 ± 11 years) were dissected to leave the menisci, cruciate ligaments, posterior joint capsule and collateral ligaments. The resected femur and tibia were rigidly secured within a test system which permitted kinematic registration of the knee using a commercially available image-free navigation system. Frontal plane knee alignment and varus-valgus stress angles were acquired. The force applied during varus-valgus testing was quantified. Medial and lateral bone-collateral ligament-bone specimens were then prepared, mounted within a uni-axial materials testing machine, and extended to failure. Force and displacement data were used to calculate the principal structural properties of the ligaments. The mean varus laxity was 4 ± 1° and the mean valgus laxity was 4 ± 2°. The corresponding mean manual force applied was 10 ± 3 N and 11 ± 4 N, respectively. While measures of knee laxity were independent of the ultimate tensile strength and stiffness of the collateral ligaments, there was a significant correlation between the force applied during stress testing and the instantaneous stiffness of the medial ( r  = 0.91, p  = 0.001) and lateral ( r  = 0.68, p  = 0.04) collateral ligaments. These findings suggest that clinicians may perceive a rate of change of ligament stiffness as the end-point during assessment of collateral knee laxity.